Actinidia chinensis Planch. Improves the Indices of Antioxidant and Anti-Inflammation Status of Type 2 Diabetes Mellitus by Activating Keap1 and Nrf2 via the Upregulation of MicroRNA-424. (31st May 2017) - Sun, Longfeng; Li, Xiaofei; Li, Gang; Dai, Bing; Tan, Wei
Abstract : The fruit juice of Actinidia chinensis Planch. has antioxidant and anti-inflammation properties on patients with type 2 diabetes mellitus (T2DM), but the molecular mechanism was unclear. The patients took the juice and the serum level of antioxidant miR-424, Kelch-like ECH-associated protein 1 (Keap1), erythroid-derived 2-like 2 (Nrf2), and biochemical indices were measured. The juice increased the levels of serum microRNA-424, Keap1, and Nrf2 and reduced the levels of interleukin-1 (IL-1) beta and IL-6 in T2DM patients. The levels of SOD and GSH were higher while the levels of ALT and AST were lower in the patients consuming the juice when compared to the patients without taking the juice. The Spearman rank correlation analysis showed that the serum levels of miR-424 were positively related to Keap1 and Nrf2 levels while Keap1 and Nrf2 levels were positively related to the levels of SOD and GSH and negatively related to IL-1 beta and IL-6. Thus, FJACP improves the indices of antioxidant and anti-inflammation status by activating Keap1 and Nrf2 via the upregulation of miR-424 in the patients with T2DM. This trial is registered with ChiCTR-ONC-17011087 on 04/07/2017.